1991
DOI: 10.1159/000174773
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Elevation of the Aldosterone/Plasma Renin Activity Ratio in Hypertensive Patients with Increases of 11-Deoxycorticosterone and 18-Hydroxy-ll-Deoxycorticosterone: A Subtype of Essential Hypertension?

Abstract: Among 436 patients with hypertension unrelated to any renal lesion, renovascular damage, pheochromocytoma, Cushing’s syndrome or hyperthyroidism, 15 patients had low plasma renin activity (PRA) and elevated plasma aldosterone concentrations in the upright position and resultant high aldosterone/PRA ratios: 8 with aldosterone-producing adenoma (APA; group 1) and 7 with idiopathic hyperaldosteronism (IHA; group 2). Thirtynine patients had suppressed PRA in the presence of normal plasma aldosterone levels and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…CT measurements of the adrenal glands were made to the nearest millimeter and multiplied by an appropriate magnification factor to obtain the true size, according to the method described by Montagne et al [8] ( Fig. 1) with a minor modification [19]. The width of the gland was defined as the greatest linear dimension seen on any single tomographic section (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CT measurements of the adrenal glands were made to the nearest millimeter and multiplied by an appropriate magnification factor to obtain the true size, according to the method described by Montagne et al [8] ( Fig. 1) with a minor modification [19]. The width of the gland was defined as the greatest linear dimension seen on any single tomographic section (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1). The length of the gland was defined as its cephalocaudal dimension and was determined by counting the number of sections on which the adrenal gland was visible and multiplying the number by the true interval on the CT scan according a modification of the method [19]. Adrenal measurements in control subjects with Cushing's syndrome or APA were made on the contralateral sides of the adrenal tumors.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that 12.4% of 436 Japanese hypertensive patients had low plasma renin activity (PRA) combined with a normal plasma aldosterone concentration (PAC), resulting in an elevated ratio of PAC to PRA (PAC/PRA), 5,6 and we found that so-called pressure natriuresis was incomplete in this subgroup of patients. 6,7 The inappropriate elevation of aldosterone in such hypertensive individuals suggests persistent mineralocorticoid synthesis despite minimal stimulation of RAS.…”
mentioning
confidence: 86%
“…14 Under normal conditions, the PAC was 110 to 555 pmol/L, and the PAC/PRA ratio was Ͻ830 pmol/L per ng ⅐ mL Ϫ1 ⅐ h Ϫ1 . 5,6,14 To facilitate analysis, hypertensive patients were divided into groups with elevated PAC/PRA ratios (low-renin hypertension) or normal to low PAC/PRA ratios (normalor high-renin hypertension). 5,6 Detection of CYP11B2 Gene Polymorphisms Genomic DNA was prepared from peripheral white blood cells according to a standard column extraction technique (Qiagen).…”
Section: Pac/pra Ratiomentioning
confidence: 99%
“…Approximately 10% to 20% of patients with essential hypertension exhibit high ALD/PRA. In a study by Komiya et al, 1 which characterized the renin profile in 421 Japanese patients with essential hypertension, 39 patients exhibited a high (Ͼ30) ALD/PRA. The genes for the enzymes involved in aldosterone biosynthesis may contribute to low-renin hypertension.…”
mentioning
confidence: 99%